2022
DOI: 10.3390/foods11131914
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Spoilage Activity and Exopolysaccharides Production by Selected Lactic Acid Bacteria

Abstract: In this study, eight lactic acid bacteria (LAB) strains, previously isolated from traditional and gluten-free sourdoughs, and selected for their potential in improving the sensory and rheological quality of bakery products, were screened against some common spoilage agents. The anti-mould activity was tested using strains of the species Fusarium graminearum, Aspergillus flavus, Penicillium paneum and Aspergillus niger. Regarding the antibacterial activity, it was assessed against four strains of the species Es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…The comparatively lower negative correlation coefficient between the numbers of E. coli and LAB, on the other hand, suggested that the inhibition effect on E. coli by LAB growth during the pickle fermentation was indirect. Similar results were reported previously (Iosca et al, 2022;Yang et al, 2014).…”
Section: Model Parameter Estimation and Statistic Methodssupporting
confidence: 93%
“…The comparatively lower negative correlation coefficient between the numbers of E. coli and LAB, on the other hand, suggested that the inhibition effect on E. coli by LAB growth during the pickle fermentation was indirect. Similar results were reported previously (Iosca et al, 2022;Yang et al, 2014).…”
Section: Model Parameter Estimation and Statistic Methodssupporting
confidence: 93%
“…Five strains were provided by the Unimore Microbial Culture Collection (UMCC), University of Modena and Reggio Emilia (Italy), and the remaining strains were provided by the National Food Institute Culture Collection (NFICC), Technical University of Denmark (Table 1). UMCC strains were identified and characterized by 16 s RNA gene sequencing in previous works and selected for their antispoilage activity [14,15]. Regarding NFICC strains, they were identified by using the MALDI Biotyper ® sirius IVD System (BRUKER, Roskilde, Denmark) or through whole-genome sequencing, and selected for their suitability to ferment plantbased substrates [23].…”
Section: Lactic Acid Bacteria Strainsmentioning
confidence: 99%
“…Ideally, the need for alternative preservatives should be obtained from naturally occurring sources that can be achievable using microorganisms or/and their metabolites [13]. In this context, selected lactic acid bacteria (LAB) can be exploited to prevent spoilage of bread and contribute both to the production of sensory properties and microbial safety of bakery products [14,15]. The use of LAB as a starter culture has a long history in a variety of fermented foods.…”
Section: Introductionmentioning
confidence: 99%
“…During bread storage, the microbial load of breads varied. The reasons might be variation in antimicrobial metabolite production (Iosca et al, 2023), acidification rate, and organic acid type and amount production (Sarac & Ahmet, 2022). The bread production process (Jasper et al, 2022), bread processing environment (air), and bread ingredients contributed to the microbial contamination of breads (Juliana et al, 2016).…”
Section: Microbial Load Of Breadsmentioning
confidence: 99%